Determinación de la Eficiencia del sistema integrado de administración financiera (Siaf) en la Municipalidad distrital de San Martín de Alao, provincia de el Dorado, departamento de San Martín - Reátegui Ruiz, Beatriz (2006)
In the present work of investigation there is analyzed information referred to the importance of the municipalitiesin the managing of the budget for the development of the communities, by means of the utilization of the SIAF-GL. The Municipality of San Martín de Alao, located in the District of the same name, Province of El Dorado, Department of San Martin, on initiative of his authorities and in coordination with the Department of Economy and Finance, is implementing, from January, 2006, the lntegrated System of Financial Administration for Local Governments (SIAF-GL), in order to favor the managing of the budgetary resources in his different phases of Commitment, Earned, Turned and Paid, generating daily information like that of income and expenses, to allow to his authorities to analyze his management taking actions of control in opportune form and hereby to contribute to the development of his locality. The evaluation of the Efficacy and Efficiency of the managing of the budget in the first semester on the part of the Municipality of San Martín de Alao, demonstrates that modifications were realized to the institutional Budget of Opening to be able to expire with the foreseen in the management of the Mayor during this half-yearly period. The present work is constructed by chapters referred to the introduction, Marco Teórico, Methodology, Obtained Results and Conclusions and Recommendations.